1D simulation of blood flow characteristics in the circle of Willis using THINkS. Issue 4 (12th March 2018) - Huang, George P.; Yu, Hongtao; Yang, Zifeng; Schwieterman, Ryan; Ludwig, Bryan
Abstract: One-dimensional (1D) simulation of the complete vascular network, so called THINkS (T otalH umanI ntravascularN etwork S imulation) is developed to investigate changes of blood flow characteristics caused by the variation of CoW. THINkS contains 158 major veins, 85 major arteries, and 77 venous and 43 arterial junctions. THINkS is validated with available in vivo blood flow waveform data. The overall trends of flow rates in variations of the CoW, such as the missing anterior cerebral artery (missing-A1) or missing posterior cerebral artery (missing-P1), are confirmed by in vivo experimental data . It is demonstrated that the CoW has the ability to shunt blood flow to different areas in the brain. Flow rates in efferent arteries remain unaffected under the variation of CoW, while the flow rates in afferent vessels can be subject to substantial changes. The redistribution of blood flow can cause particular vessels to undergo extra flow rate and hemodynamic stresses.